The wonder of our neuromotor system and the technological challenges they pose - Abdul Rashid, Abdul Hamid (2005)
As we go along in life, we perceive many types of sensation both from inside our body and from the environment. Perception leads tb decision, including how to react. This leads to purpose or objective, and actual physical deed is done by movement of particular parts of our body. This is the action; which may be accomplished in accordance to our will or performed automatically, by reflex. Movements range from very fine and precise, such as those performed by fingers and eye rotating muscles, to the very powerful and deliberate such as those done by the leg muscles. The work of muscles has three main aspects: direction and range of movement; strength required; and speed at which movement is done. All these are controlled by the nervous system. Nervous system together with the muscular system is called neuromotor system. It is in fact the most complex and most intricate system in our body and made up of billions of nerve cells called neurons. In order to perform a specific task, a specific group of muscles and type of muscle fibres controlled by a specific component of the nervous system is needed. This has been confirmed by the author and his co-researchers from their studies on neuromotor system. Any structure of our body can be damaged by any cause. Some damaged structures regenerate by themselves. However, the nervous tissue once formed will never regenerate when destroyed. Accordingly, as a therapeutic measure, Stem cells or olfactory mucosa from the nose are transplanted into the damaged area of the nervous system; so that they can grow and replace the damaged nervous tissue. Until the last few decades or so, this has been one of the most widely accepted facts of Medicine. Although there is some degree of regaining function in patients with injury or derangement of nervous system, complete restoration of functional status as normal has not been achieved. There can be many reasons for such outcome. One of the reasons is, as mentioned above, highly specific and complex neuromotor system is needed to perform a specific muscle function. Such a complex system is after all created by none other than the Almighty. With present day technology, are we ready to fully accomplish what our Creator created?